Deformation and fracture of 3D printed disordered lattice materials: Experiments and modeling. (15th January 2019) - Xu, Yading; Zhang, Hongzhi; Šavija, Branko; Chaves Figueiredo, Stefan; Schlangen, Erik
Abstract: A method is presented to model deformation and fracture behavior of 3D printed disordered lattice materials under uniaxial tensile load. A lattice model was used to predict crack pattern and load-displacement response of the printed lattice materials. To include the influence of typical layered structures of 3D printed materials in the simulation, two types of printed elements were considered: horizontally and vertically printed elements. Strengths of these elements were measured: 3 mm cubic units consist of lattice elements with two printing directions were printed and their strengths were tested in uniaxial tension. Afterwards, the measured element strengths and bulk material strength, respectively, were used as model input. Uniaxial tensile tests were also performed on the printed lattice materials to obtain their crack pattern and load-displacement curves. Simulations and experimental results were comparatively analyzed. For both levels of disorder considered, only when measured strengths were assigned to the elements with identical printing direction, are the predicted crack patterns and load-displacement curves in agreement with experimental results. The results emphasize the importance of considering printing direction when simulating mechanical performance of 3D printed structures. The influence of disorder on lattice material mechanical properties was discussed based on the experiments and simulations. Graphical abstract: Highlights: Three-dimensional disordered lattice materials have been designed and printed using fused deposition modeling. Fracture performance of the printed lattice material is simulated by an experiment informed discrete model. The influence of printing directions on the lattice material can be captured by the discrete lattice model. The influence of disorder degree on the printed materials is experimentally and numerically clarified.